BENTUK DAN FUNGSI MUSIK GONDANG SABANGUNAN BATAK TOBA PADA GRUP HORAS RAPOLO MUSIK DI SEMARANG (Jurnal Seni Musik, 2015)
Horus Rapolo Musik is one of the musical group Batak Toba is located in Semarang. In the show performed always using taganing as a hallmark of Batak music. In Batak music, Gondang Sabangunan has several functions and uniqueness, making the Sabangunan Gondang interesting to study. Aside from the function, the shape of Gondang Sabangunan is also important to investigate. The targets of this research are the shape and function of the ensemble Gondang Sabangunan Horas Rapolo Musik. Data was collected by observation, study of documents and interviews. A data analysis technique is done with the following steps: (1) data collection, (2) Reduction of data, (3) Presentation of Data, (4) Withdrawal Conclusions. The results showed that the shape of the composition of the ensemble Gondang Sabangunan Horas Rapolo music is no longer the same as the form of the existing arrangement in Tapanuli. In ensemble Gondang Sabangunan on Horas Rapolo Music has several functions, namely (1) the function of the disclosure emotional, (2) the function of the appreciation of ethnic, (3) the function of entertainment, (4) communication functions, (5) the function of symbolism, (6) function Raksi and physical, (7) functions related to social norms, (8) the attestation function of social institutions and religious ceremonies, (9) the function of cultural continuity and (10) the function penginteraksian society. Based on the research results, it can be concluded that this form of music in ensemble Gondang Sabangunan Horas Rapolo Musik is no longer the same as the structure of the instrument of yore. This is consistent with the development, where its always sarune formerly used as a melody on Gondang Sabangunan, at this point has been very rarely used.